COMPARATIVE MORPHOLOGICAL AND ANATOMICAL STIDY OF LINUM GENUS: LINUM NERVOSUM WALDST. AND LINUM LUTEOLUM BIEB. OF LINACEAE S.F. GRAY. - F. K. Serebryanaya; E. I. Kozlova; S. G. Popova (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2015)
Macro-morphological features of Linum nervosum Waldst. and Linum luteolum Bieb. were examined in this study. Diagnostic signs of a root, stem, leafstalk and lamina structure were revealed. The obtained data can be used in further systematic researches of the Linum genus.